Exploring the Use of Short Films in A Deep Learning Oriented EFL Listening Classrooms: A Qualitative Case Study - Dessy Kurniasy; Zahratul Idami; Shafrida Wati; Wahidah (Jumper: Journal of Educational Multidisciplinary Research, 2026)
Listening comprehension continues to present significant difficulties for English as a Foreign Language (EFL) learners, especially when they must process spoken language in real time. The audiovisual media in listening instruction can improve comprehension and learning engagement. This study investigates how short films are used in a deep learning approach in a university English as a Foreign Language (EFL) listening class. A qualitative case study method was used, involving twenty-two undergraduate students in a Listening and Speaking course at the State Islamic Institute (IAIN) Langsa, Indonesia. Classroom observations, student reflection logs, and semi-structured interviews were used to gather the data. The training unfolded over four separate sessions. The project involved watching films, identifying important words, creating stories, and writing personal reflections. The findings indicated that the incorporation of short films improved students' listening comprehension by providing contextual visual cues that facilitated meaning construction. Moreover, the use of reflective activities encouraged deeper cognitive involvement, allowing students to connect the film's content with their own experiences and the larger societal context. Conversely, some students encountered difficulties in spontaneous oral retelling, attributable to limited vocabulary and speaking confidence. In conclusion, the study indicated that the combination of audiovisual materials with deep learning activities can cultivate more meaningful listening experiences within EFL classrooms.